PENGEMBANGAN PENDIDIKAN KECAKAPAN HIDUP DI KALANGAN SANTRI - Samsul (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2016)
Education is a conscious and deliberate effort to create an atmosphere of learning and the learning process so that learners are actively developing the potential for him to have the spiritual strength of religious, self-control, personality, intelligence, noble morality, as well as the skills needed him, society, nation and state. Development of life skills education which consists of cognitive skills, affective and psychomotor development is an activity in shaping students' creativity.